Prevalence and diversity of Borrelia spp. in questing ticks from urban green spaces in Lithuania - Justina Snegiriovaitė; Indrė Lipatova; Miglė Razgūnaitė; Algimantas Paulauskas; Jana Radzijevskaja (Ticks and Tick-Borne Diseases)
Lithuania is a highly endemic area for Lyme borreliosis (LB), and Ixodes ricinus, the primary vector of Borrelia burgdorferi sensu lato (s.l.) in Europe, is widespread throughout the country. While previous studies conducted in Lithuania have examined the prevalence of B. burgdorferi s.l. in natural habitats, comprehensive data on the distribution of ticks and their infection with tick-borne pathogens in urban areas remain largely unknown. This study aimed to assess the risk of LB by analyzing tick abundance and the prevalence of Borrelia spp. in ticks collected from urban green spaces across ten Lithuanian counties. A total of 3628 ticks were collected, comprising two species: I. ricinus (n = 3599) and Dermacentor reticulatus (n = 29). Ticks were found in 43 out of 52 investigated locations. Molecular analyses detected B. burgdorferi s.l. in 22.89 % of I. ricinus and 3.45 % of D. reticulatus specimens, while Borrelia miyamotoi was found in 3.97 % of I. ricinus and 3.45 % of D. reticulatus. Five species from B. burgdorferi s.l. complex were identified: B. afzelii, B. garinii, B. burgdorferi s.s., B. lusitaniae, and B. valaisiana. Co-infections with different Borrelia spp. were observed in 0.72 % of I. ricinus ticks. Borrelia-infected ticks were detected at 38 of 43 locations (88.37 %), with the prevalence of infection ranging from 3.70 % to 41.53 %. These findings indicate that urban green spaces in Lithuania provide suitable habitats for ticks, with varying risks of human-tick contact and tick-borne infections, underscoring the potential public health risk of LB in Lithuanian cities. Further evaluation of tick distribution and the prevalence of Borrelia spp. is necessary to monitor how climate change and urbanization affect pathogen circulation and infection risk.